BRANCH PROFIT OF UPSTREAM OIL AND GAS BASED ON TAX TREATY AND PRODUCTION SHARING CONTRACT IN INDONESIA - Tambunan, Maria R. U. D. (Faculty of Law, Parahyangan Catholic University, 2024)
Tax treatment for a production sharing contract (PSC) is possibly different from general tax rules when calculating the amount of annual cost to be allocated by upstream oil and gas business to project their profit. On the other hand, the prevailing tax law applied in a particular country could either be made based on domestic tax law and a tax treaty depends on the tax subject. This article is intended to discuss tax arrangements sourced by a PSC during cost recovery regime and tax treaties in Indonesia. This study also discusses the cases brought before the Supreme Court due to the interplay of a PSC and a tax treaty during the years of 2015-2021. The research uses normative legal research with data collected through documentation studies. The contractors demanded a reduced tax rate on branch profit derived from a tax treaty as a general rule considering that they are the persons covered by the treaty. However, they must also respect production sharing as agreed in a PSC that existed before the conclusion of the tax treaty. For the future, it needs to adopt the stabilization clause to deal with the issue.